AB1107 COMPLEMENTARY AND ALTERNATIVE MEDICINE USAGE IN PATIENTS WITH FAMILIAL MEDITERRANEAN FEVER. (June 2019) - Colak, Seda; Tekgoz, Emre; Cinar, Fatma İlknur and Yilmaz, Sedat and Çınar, Muhammet
Abstract : Background: Familial Mediterranean Fever (FMF) is the most common hereditary, chronic autoinflammatory disease. Colchicine is the mainstay of the treatment, which reduces frequency of attacks and amyloidosis risk. Complementary and alternative medicine (CAM) therapies can be a non-mainstream treatment choice in chronic diseases. Frequency of use of CAM therapies among patients with FMF is not established yet. Objectives: In the current study we aimed to identify the prevalence of the patients using CAM therapies and the factors associated with CAM usage among the patients with FMF. Methods: One hundred and sixty-five patients were included in the study. Data regarding demographic, social and clinical characteristics were obtained from the patients. The patients were asked whether they were using any type of CAM and if they had suffered harm and/or benefit. The treatment adherence of the patients was assessed using by Morisky Green Levine Scale (MGLS). The Beliefs About Medicines Questionnaire (BMQ-T) was used to assess patient's beliefs about medicines. Results: Fifty-six (33.9%) patients declared to use at least one CAM. The mean age of the patients was 34.1 ±12.7 years and the mean disease duration was 16.8±10.8 years. The mean dose of colchicine was 1.4±0.4 mg/day. Patients with concomitant disease and positive history of FMF in relatives had higher rates of using of CAM (p=0.011 and p=0.014 respectively). There was no statistically significance between age, sex, marital, socioeconomic and working status, difficulty of access to the treatment center, dose of colchicine, adverse events related to colchicine, attack frequency and disease severity of the patients and frequency of CAM using (p>0.05). The most frequently chosen types of CAM modalities were massage therapy (12.1%), imagining (9.7%), relaxation techniques (9.1%), cupping (9.1%) and natural products (9.1%). It is found that 42 (75.0%) of patients reported that they have suffered benefit from CAM. The mean duration of the using of CAM was 7.9 ±6.4 years. According to the BMQ-T, there was higher rate of concern about colchicine among patients that were using CAM (p=0.035) (Table 1 ). There was no statistically significance between compliance with colchicine treatment and using of CAM (p=0.313). Conclusion: Colchicine is the gold standard of treatment because of the known effect of colchicine treatment on the severity and frequency of FMF attacks and the risk of development of amyloidosis. Approximately one third of patients with FMF were using at least one of the CAM modalities in the current study. Concerns about colchicine treatment may have increased the tendency to use CAM therapies. On the other hand, patients should be informed that CAM therapies should not be an alternative to colchicine. Disclosure of Interests: None declared